E-034 Single-center experience with the celt acd vascular closure device for neurointerventional procedures. (22nd July 2018) - Kuhn, A; de Macedo Rodrigues, K; Rex, D; Massari, F; Wakhloo, A; Puri, A
Abstract : Introduction/purpose: Vascular closure devices have been designed to provide immediate sealing of the arterial puncture site after catheter-based angiography. The Celt ACD (Vasorum, Dubline, Ireland) is a novel stainless-steal arterial closure device which received FDA approval in 2016. The device is available in 3 sizes (5, 6 and 7 French) and is delivered by a disposable, single-use unit through the femoral sheath. We prospectively evaluated safety and efficacy of this new vascular closure device in our neurointerventional patient population. Materials and methods: A total of 37 patients were included in our study between December 2017 and January 2018. All interventionalists have familiarized themselves with the device prior to usage. We evaluated device deployment feasibility, patient discomfort during deployment, device safety and efficacy in patients undergoing a variety of neurointerventional procedures. Results: A total of 37 patients (20 females) with a mean age of 60 years (range 23–90 years) were included. The sheath was placed in the common femoral artery in the majority of cases (36/38). Femoral access ranged from 5 to 8 French. There were 24 elective diagnostic angiograms, 4 angiographic evaluations for SAH, 6 stroke interventions and 4 stenting/flow diverter placement procedures. Two of the stroke patients had received tPA. Twelve patients were on aspirin 81 mg or 325 mg daily and 8 patients were on dual antiplatelet therapy (aspirin 81 mg and Plavix 75 mg). Eleven patient were not on any form of anticoagulation/platelet inhibition. The remainder of the patients was either on Coumadin (therapeutic to sub-therapeutic levels), other anticoagulants such as Eliquis or a combination thereof with aspirin. Device deployment was successful in 33/38 cases (86.8%) and immediate hemostasis was achieved. Patients did not complain of pain or unusual discomfort with device deployment or during the recovery period. Inability to deploy the device occurred in a total of 4 cases (10.5%) due to operator failure (n=3) and in one case because the patient moved during release of the device. Major complication post device deployment was seen in one patient who was seen for a diagnostic angiogram prior to intervention. A Celt ACD device was used for closure after each procedure. This patient developed a large femoral hematoma and pseudoaneurysm likely due to vessel laceration which did not require surgical repair. Conclusion: The Celt ACD vascular closure device is a good alternative to previously available closure devices. Disclosures: A. Kuhn: None. K. de Macedo Rodrigues: None. D. Rex: None. F. Massari: None. A. Wakhloo: 1; C; Philips Healthcare. 2; C; Stryker Neurovascular. 3; C; Harvard Postgraduate Course, Miami Cardiovascular Institute. 4; C; NeuroIncCo. A. Puri: 1; C; Stryker Neurovascular. 2; C; Cadman Neurovascular, Stryker Neurovascular, Covidien. 3; C; Miami Cardiovascular Institute. 4; C; NeuroIncCo.